Effect of Orange Peel (Citrus sinensis) (L) extrcts and powder on confused flour beetle Tribolum confusum (Coleoptera: Teneberionidae) - Yunis, May Ibrahem (Iraqi Journal of Science, 2023)
This study was carried out to determine the effect of extras of orange peel of (Citrus sinensis) in concentrations (1,5, 10) % as well as stomachic effect for the powder of the plant with doses of 5,10 , 15/gm on the biological activities of the adults of Tribolim confusum . The effect of powder from the adults has been evaluated using different concentrations of the orange peel. The results showed that the powder have significant effect on the mortality rates of adults. and caused reduction in number of adults after 3 days with 5,10,15/gm killed (30,40, 43.3)% respectively. The use of different doses of Citrus sinensis peels powder not impact significantly after just one day. The extract of essential oil also caused growth inhibition in adults and showed that extracts were more effective than the powder. Increasing the essential oil concentration and exposure time lead to increased the mortality rate of adult. The mortality reaches to 100% after 3 days when insect tested with 10% of extract. Generally, the results of this study showed effect of any form of Citrus sinensis peel on adult of Tribolium confusum compared with control treatment. the effectiveness of orange peel powder is probably due to silica or silica like component, which are abrasive and the ability of the particles to adhere to the grain. Citrus sinensis peel oil was superior to untreated and powder using 99.00% reduction in adult emergence at use 0.75g.